Implantación de un Sistema Contable en el Hostal “MIRADOR” de la Ciudad de Loja, período Abril-Junio del 2016 - Matailo Bazarán, Yadira Fernanda (2017)
The present thesis was carried out to meet the General Objective set forth as: IMPLEMENT A ACCOUNTING SYSTEM IN THE HOSTAL "MIRADOR" OF THE CITY OF SHOP PERIOD APRIL-JUNE 2016, in order to obtain accounting information, truthful and timely to facilitate To its owner the decision making, for the normal development of the company. For the fulfillment of the specific objectives, the physical verification of all the assets of the company was carried out, determining the initial inventory and the initial situation; As well as gathering information and documents necessary to order them chronologically, in order to register operations in an orderly manner. Next, a plan and a manual of the accounts according to the needs of the company were established, which can be identified during the accounting process; Subsequently registered each of the transactions carried out by the company to obtain financial results that help the management decision making, for it was made a memorandum of the operations of which are backed with the source documentation, facilitating its registration in the Book Journal, Mayor General, Check Balance, Worksheet to conclude with all financial statements that reflect the economic and financial situation of the company., the respective conclusions and the recommendations on the most relevant ones of the 5 same were elaborated, which constitute a contribution with the purpose of contributing to the development and improvement of the company. The fundamental conclusion to which the current work of thesis has been completed is that the implementation of the accounting process was fundamental for the development of the company, since it is structured in a real information base of the Hostel, so that the property uses As To safeguard resources that improve economic solvency.